Pendidikan Qur’an Hadis Berwawasan Integratif Inklusif - Lidyaningsih, Windy; Misbah, M. (Jurnal Kependidikan, 2024)
The learning of Islamic Religious Education delivered in schools still impresses that this subject only stands alone and only teaches worship and sharia. Even though the content of the material in Islamic Religious Education has a relationship and teaches mutual respect. So there needs to be an understanding that Islamic Religious Education is not a subject that only stands alone and causes a dichotomy of science. The purpose of the study is to understand the material of Islamic Religious Education, especially in the Qur'an and Hadist families that are intergative and inclusive. The research method used is qualitative descriptive by collecting research data sources from libraries such as journals, books, documents, and other freelance articles. The result in this study is the content in the Qur'an and Hadith which in itself has an inclusive and integrative insight. This requires a deep understanding so that you can know what verses of the Qur'an and Hadith are inclusive and integrative. This proves that the Qur'an and Hadith as scientific sources need to be tested for truth through scientific aids. For example, Surah An-Nur verse 43 regarding the process of rain that can be integrated with natural science. Then in Surah al-Kafirun verse 6 which means "for you your religion and for me my religion" here that there is no compulsion in religion and mutual respect for differences in adhering to religion. Keywords: Education, Qur'an Hadith, Integrative, Inclusive